A Study on Reproductive Biology of Osteochilus wandersii from the Rokan Kiri River, Rokan Hulu Regency, Riau Province - Dewi Sartika; Ridwan Manda Putra; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Osteochilus wandersii or lelan fish is a type of freshwater fish that inhabit the Rokan Kiri River. This fish has high economical value, around Rp 30.000-50.000/Kg. However, information on its biological aspects, especially the reproductive biology is poorly known. To understand the reproductive biology of this fish, a study has been conducted from February to April 2015. Total fish captured was 168 (76 males and 92 females). Sex ratio between male and female was 1:1.2. The GSI of male was 0.45%-0.88% and that of the female was 0.82%-3.86%. The fecundity of the fish were 5,772-9,087 eggs/fish. Egg diameter was 0.2-0.8 mm. The relationship between fecundity and standart lenght was y = 1.379x + 0.883, fecundity and body weight was y = 0.581x + 2.858 and the fecundity with ovary weight y = 0.596x + 3.582. The water quality parameter shown are as follows: temperature 26-28°C, transparency 21.5-41.5 cm, pH 6, DO 5.6-7.8 mg/L, CO2 3.9-5.9 mg/L, and current speed 0.40-0.64 m/s. Data on water quality parameters indicate that water quality in the Rokan Kiri River is able to support the life of the fish.Keyword: Osteochilus wandersii, Rokan Kiri River, GSI, fecundity, and eggs diameter